2010
DOI: 10.1056/nejmoa0907897
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Ancestry in Lung-Function Predictions

Abstract: BACKGROUND Self-identified race or ethnic group is used to determine normal reference standards in the prediction of pulmonary function. We conducted a study to determine whether the genetically determined percentage of African ancestry is associated with lung function and whether its use could improve predictions of lung function among persons who identified themselves as African American. METHODS We assessed the ancestry of 777 participants self-identified as African American in the Coronary Artery Risk De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

16
231
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(250 citation statements)
references
References 44 publications
16
231
3
Order By: Relevance
“…The mean absolute differences in predicted FEV1 observed between models with or without European ancestry were smaller than those observed in African Americans [5]. The French Canadian population is known to have less genetic heterogeneity than most general European populations [9].…”
Section: Genome-wide Genetic Ancestry Measurements To Predict Lung Fumentioning
confidence: 68%
See 2 more Smart Citations
“…The mean absolute differences in predicted FEV1 observed between models with or without European ancestry were smaller than those observed in African Americans [5]. The French Canadian population is known to have less genetic heterogeneity than most general European populations [9].…”
Section: Genome-wide Genetic Ancestry Measurements To Predict Lung Fumentioning
confidence: 68%
“…Compared to self-reported race and/or ethnicity, genetic data can provide more accurate and objective measurements of ancestry and has the potential to alleviate some of the problems related to the lack of consensus on the definition of race and ethnicity worldwide [4]. A recent report suggested that genetically determined ancestry improves predicted lung-function measurements in African Americans [5]. Here, we test whether genetic ancestry derived from genome-wide genotyping data is useful to predict lung function in a diverse European population.…”
Section: Genome-wide Genetic Ancestry Measurements To Predict Lung Fumentioning
confidence: 99%
See 1 more Smart Citation
“…KUMAR et al [33] concluded that genetic variation affects lung volumes. In self-identified African Americans, in whom there is considerable ancestral admixture with genes from Europeans, they found a significant inverse association between lung function and African ancestry, but SES and environmental factors were not taken into account.…”
mentioning
confidence: 99%
“…Ethnic differences in lung function were first reported over 150 years ago [4] and have been variously ascribed to differences in body physique, socioeconomic circumstances, environmental exposures and/or genetic ancestry [4][5][6][7][8][9][10]. Interpretation of these studies is complicated not only by differences in methodology, study population and sample size but by the complexities of defining 'race' or 'ethnicity' in an increasingly multiethnic society [4,6,7,11,12]. While self-identification remains the accepted standard for defining race and ethnicity, this rarely makes any adjustment for admixture (i.e., mixed parentage).…”
mentioning
confidence: 99%